2019
DOI: 10.2134/agronj2018.03.0213
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops and Returning Residue Impact on Soil Organic Carbon, Bulk Density, Penetration Resistance, Water Retention, Infiltration, and Soybean Yield

Abstract: Johnson et al., 2016). Removal of crop residue reduces soil organic carbon (SOC), and impacts soil productivity. However, the impacts of residue removal rates on soils depend on certain factors such as soil texture, soil topography, initial contents of SOC, tillage, and cropping system (Blanco-Canqui et al., 2013). Water is the most limiting factor for crop production in regions where either irrigation is not available or precipitation is limited (Das et al., 2017). Water stored in the soil profile helps to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
2
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 51 publications
8
77
2
20
Order By: Relevance
“…The equal or greater amounts of stored soil water under cover crop treatments compared to fallow in the present research might be a result of many factors other than rainfall. Possible improvements in soil physical properties due to cover crops might have increased infiltration and soil water retention [8,25,56,57]. Chalise et al [8] found that volumetric water content in plots with cover crops was higher than that in plots with no cover crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The equal or greater amounts of stored soil water under cover crop treatments compared to fallow in the present research might be a result of many factors other than rainfall. Possible improvements in soil physical properties due to cover crops might have increased infiltration and soil water retention [8,25,56,57]. Chalise et al [8] found that volumetric water content in plots with cover crops was higher than that in plots with no cover crops.…”
Section: Discussionmentioning
confidence: 99%
“…Possible improvements in soil physical properties due to cover crops might have increased infiltration and soil water retention [8,25,56,57]. Chalise et al [8] found that volumetric water content in plots with cover crops was higher than that in plots with no cover crops. For example, volumetric water content at 0-5 cm depth was 16% higher under cover crop treatment than under no-cover crop treatment at 42 d after planting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation farming (CF), a set of practices including i) minimum or no tillage ii) retention of crop residues and iii) crop rotation, has been suggested as a way to increase soil organic C (SOC) if its three principles are strictly applied [8][9][10][11]. CF in the form of planting basins has been promoted among small-scale farmers in countries like Zambia for more than two decades [12] with yield benefits for farmers if combined with complementary practices such as the use of improved crop varieties, adequate weed and pest control, among others [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Tillage, C and N inputs, crop management systems, and crop type impact SOM turnover (Kong and Six, 2010; Ghimire et al, 2017; Chalise et al, 2019; Johnson, 2019; Karlen et al, 2019). Strategies for increasing SOC in organic systems include incorporating cover/green manure crops, diversifying rotations, growing perennial crops, applying manure and other organic amendments and reducing tillage (Teasdale et al, 2007; Kong et al, 2005; Stockmann et al, 2013; Ghimire et al, 2017).…”
Section: Soil Biology and Nutrient Cyclingmentioning
confidence: 99%